2023
DOI: 10.7717/peerj.15358
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive identification and expression analysis of CAMTA gene family in Phyllostachys edulis under abiotic stress

Abstract: Background Calmodulin-binding transcription factor (CAMTA) is a major transcription factor regulated by calmodulin (CaM) that plays an essential role in plant growth, development and response to biotic and abiotic stresses. The CAMTA gene family has been identified in Arabidopsis thaliana, rice (Oryza sativa) and other model plants, and its gene function in moso bamboo (Phyllostachys edulis) has not been identified. Results In this study, a total of 11 CAMTA genes were identified in P. edulis genome. Conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Consequently, considerable progress has been achieved in understanding its molecular stress responses [ 14 , 15 , 16 , 17 , 18 , 19 ]. Through this research, numerous stress-related genes, including circular RNAs, have been identified in Moso bamboo under stress conditions [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. These findings suggest that Moso bamboo exhibits an intricate adaptation mechanism to modify phenotypic traits when faced with stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, considerable progress has been achieved in understanding its molecular stress responses [ 14 , 15 , 16 , 17 , 18 , 19 ]. Through this research, numerous stress-related genes, including circular RNAs, have been identified in Moso bamboo under stress conditions [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. These findings suggest that Moso bamboo exhibits an intricate adaptation mechanism to modify phenotypic traits when faced with stress conditions.…”
Section: Introductionmentioning
confidence: 99%